PENGGUNAAN DIRECT INSTRUCTION MODEL UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA MATERI TUMBUHAN DAN FUNGSINYA SISWA KELAS IV A SDN 015 SUNGAI SALAK KECAMATAN TEMPULING - Garnawati Siregar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
Problems in the Classroom Action Research (PTK) is the low learning outcomes IPA A fourth grade students of SDN 015 Sungai Salak Kecamatan Tempuling. This study addressed the problem by applying direct instrucsion models. The problem of this research is "Is the direct application of the model intruction IPA can improve learning outcomes in grade IV A SDN 015 Sungai Salak Kecamatan Tempuling ?. The purpose of this study is to improve science learning outcomes in class IV A SDN 015 Sungai Salak Kecamatan Tempuling by way of direct intruction models. Direct intruction A model of fourth grade students of SDN 015 Sungai Salak, Kecamatan Tempuling can improve learning outcomes significantly. At first the student learning outcomes pre-cyclye is 36.00 categorized as very unfavorable; in the first cycle was 61.00 with category; and the results of the second cycle is 81.50 with very good category. Mastery learning individually and classical increases; pre-cyclye 4 students and 20.00 (not finished); in the first cycle is 12 students and 60.00% (not finished) and the second cycle is 19 students or 95% (complete). Based on observations of fourth grade students of SDN 015 A Sungai Salak Kecamatan Tempuling, activity in the first cycle an average of 72% or better and the second cycle of activity is 82% or better at all. Students seem to understand the direct intruction models and they can understand the subject matter properly and appropriately. Based on the research results with direct instructional improvement intruction models managed to fix the problem of low student learning outcomes SDN 015 class IV A Sungai Salak Kecamatan of Tempuling.